Uso das técnicas de infravermelho e de ressonância magnética nuclear na caracterização da reação ácido-base de um cimento odontológico experimental - Bertolini, Marcio José [UNESP]; Zaghete, Maria Aparecida [UNESP]; Gimenes, Rossano (Sociedade Brasileira de Química, 2009)
Glass ionomer cements (GICs) are products of the acid-base setting reaction between an finely fluoro-alumino silicate glass powder and poly(acrylic acid) in aqueous solution. The sol gel method is an adequate route of preparation of the glasses used to obtain the GICs. The objective of this paper was to compare two powders: a commercial and an experimental and to investigate the structural changes during hardening of the cements by FTIR and Al MAS NMR. These analyses showed that the experimental glass powder reacted with organic acid to form the GICs and it is a promising material to manufacture dental cements.
Use of infrared and magnetic nuclear resonance techniques in the characterization of the acid-base reaction of an experimental dental cement
Keywords: cements; polyacrylate; ionomer